Pharmacogenomics and personalized medicine: a review focused on their application in the Chinese population - Shu Wen-ying; Li Jia-li; Wang Xue-ding; Huang Min (Acta Pharmacologica Sinica; Vol 36, No 5 (May 2015): Acta Pharmacologica Sinica, 2017)
The field of pharmacogenomics was initiated in the 1950s and began to thrive after the completion of the human genome project 10 years ago. Thus far, more than 100 drug labels and clinical guidelines referring to pharmacogenomic biomarkers have been published, and several key pharmacogenomic markers for either drug safety or efficacy have been identified and subsequently adopted in clinical practice as pre-treatment genetic tests. However, a tremendous variation of genetic backgrounds exists between different ethnic groups. The application of pharmacogenomics in the Chinese population is still a long way off, since the published guidelines issued by the organizations such as US Food and Drug Administration require further confirmation in the Chinese population. This review highlights important pharmacogenomic discoveries in the Chinese population and compares the Chinese population with other nations regarding the pharmacogenomics of five most commonly used drugs, ie, tacrolimus, cyclosporine A, warfarin, cyclophosphamide and azathioprine.